A SOCIOLOGICAL ANALYSIS OF WOMEN CRIMINALS IN TURKEY: A CASE STUDY - Åžahin, Hande (European Scientific Journal, ESJ, 2015)
This study, through a questionnaire and in-depth interviews, aims to to make a sociological analysis of female criminals in the Denizli Open Prison, including their demographic characteristics, family structures, committed crimes and the factors that led to their criminal acts. The questionnaire, composed of 57 questions, has been evaluated in the SPSS program, and in-depth interviews were done with 6 female criminals for a detailed analysis of why the female criminals committed crimes and the factors that led to their behavior. In the study, the concept of crime is accepted as a social fact. The educational backgrounds, ages, families and sub- cultures of the women have been examined and the dynamics of female criminality in Turkey have been cross-examined within the limits of sampling. In the course of the study, it was found that concepts of honor, domestic violence and patriarchal structure have been key concepts of female criminality, and female criminality in Turkey can be understood in terms of these phenomena.